Effect of Processing Methods on Antinutritional Factors (Oxalate, Phytate, and Tannin) and Their Interaction with Minerals (Calcium, Iron, and Zinc) in Red, White, and Black Kidney Beans - Serkalem Abera; Weldegebriel Yohannes; Bhagwan Singh Chandravanshi (International Journal of Analytical Chemistry)
The purpose of this study was to assess how different processing techniques affected mineral compositions, antinutritional factors, and their interactions in red, white, and black kidney beans consumed in Ethiopia. Mineral contents were found to be 41–44, 58–78, and 112–126 mg Ca/100 g in the raw, soaked, and cooked samples, respectively. Iron content in the raw, soaked and cooked samples were found to be 2.77–2.97, 1.94–2.20 and 2.87–3.28 mg Fe/100 g, respectively, showing 26–30% loss on soaking followed by 33–48% increase on cooking. While Zn content in the raw, soaked and cooked samples were found to be 2.47–3.26, 3.34–4.68 and 2.83–3.31 mg Zn/100 g, respectively, showing 35–43% increase on soaking followed by 15–29% decrease on cooking. In the case of antinutrients, both treatments showed incredible decrements. Phytate in the raw samples was 178-179 mg/100 g and showed a 12–16% decrement on soaking and a 37-38% decrement up on cooking, oxalate was 1.5–1.8 mg/100 g in the raw samples and showed a 4.4–13% decrement during treatments, and tannin in the raw samples was 102–160 mg/100 g and showed a 23–30% decrement on soaking, followed by 21–41% during cooking. Phytate : Ca and oxalate : Ca molar ratios in soaked and cooked samples were within the critical values in the raw samples. In contrast, phytate : Zn and Ca × phytate : Zn in all treatments were found to be within the critical value, confirming the good bioavailability of zinc in all the samples, while phytate : Fe was found over the critical value, showing its poor availability.